New Round-Up 5: Teacher's Book - Evans V. Virginia (Harlow, Longman, 2011)
Making grammar practice fun for young learnersNew Round-Up is a seven-level course for young learners from beginner to upper-intermediate. It combines fun with systematic practice of English grammar.New Round-Up 5 includes Colourful boxes and tables to present language clearly Lively illustrated exercises to make practice fun and effective Listening tasks Translation practice English in Use sections to practise phrasal verbs, word formation, paraphrasing and idioms Regular Exam Zones CD-ROM with Exam Zones to provide more grammar and exam racticeeacher's book with answer keys, photocopiable Quizzes and Tests